A center commissioned external review of IFPRI's Development Strategy and Governance Division (DSGD) - Bromley, Daniel W.; Thomson, Kenneth J. (International Food Policy Research Institute, 2007)
The EPMR Panel saw DSGD's distinguishing elements to be: (1) taking an economy-wide approach to pro-poor development strategy work; (2) experience with long-term cross-country research; (3) a program of country-specific support activities; and (4) a focus on capacity building at the country level. It reported, however, that readers of IFPRI's work in the area were "left confused regarding the balance of and priorities of research with respect to: an economywide focus versus a sectoral focus; an agricultural focus versus a more rural focus (the rural nonfarm economy); and a territorial focus versus a sectoral focus" (Report, p. 14). "The rural economy and its integration into the national economy as well as its contribution to national growth appear[ed] to be largely missing". The Panel endorsed the Division's view that a CGEonly approach would be inadequate to address economy-wide issues, and also to learn from the combination of cross-country and country-specific studies.